Mere appearances: appearance, belief, & desire in Plato's Protagoras, Gorgias, & Republic - Storey, D (2012)
This thesis examines the role appearances play, with notable continuity, in the psychology and ethics of Plato's Protagoras, Gorgias, and Republic. Common to these dialogues is the claim that evaluative appearances are almost invariably false: what appears to be good or bad is typically not in fact so and what is good or bad typically does not appear so. I argue that this disparity between apparent and real value forms the basis of Plato's diagnoses of a wide range of practical errors: psychological phenomena like akrasia, mistaken conceptions of the good like hedonism, and the influence of cultural sources of corruption like oratory, sophistry, and poetry. It also, relatedly, forms the basis of his account of lower passions like appetite, anger, or fear. Such passions are especially prone to lead us astray because their objects -- appetitive pleasures like food, drink, or sex, for example -- present especially deceptive appearances. One of the principal aims of this thesis is to show that this presents a significant point of agreement between the psychologies of the Protagoras, Gorgias, and Republic. In all three dialogues, I argue, motivational errors result from a specific kind of cognitive error: the uncritical acceptance of appearances. Plato's early and middle psychologies differ in their account of the subject of this error -- in the Protagoras and Gorgias, the whole person; in the Republic, the appetitive or spirited part of a person's soul -- but not in their basic theory of how our passions arise or, crucially, why they are liable to motivate us towards harmful ends.